GENDER INFLUENCES DIFFERENTIATION OF CHITIN AMONG BODY PARTS. Issue 2 (13th July 2016) - Kaya, Murat; Bulut, Esra; Mujtaba, Muhammad; Sivickis, Karolis; Sargin, Idris; Akyuz, Bahar; Erdogan, Sevil
Abstract : Earlier reports have established that chitin isolates from each body part of an insect cuticle can exhibit diverse physicochemical properties. But it is still unknown if the gender of the insect can influence characteristics of chitin isolates from different body parts. The present study addresses this question. As a result, important physicochemical differences in the chitin samples from different body parts of Melolontha sp. were recorded on the basis of sex. The chitin samples were extracted from eight different body parts (antennae, head, eyes, thorax, abdomen, elytra, hindwings, and legs) of female and male. The most remarkable variations in the chitin isolates from female and male body parts were recorded in chitin content, crystallinity, thermal stability, and surface morphology. And also it was wondered these chitin isolates from different body parts of female and male could find different applications. To check this hypothesis, the chitin samples from female and male were interacted with bovine serum albumin (BSA) protein and important variations were observed.